Between the Dance that Registers and the Library that Dances, Dimenti turns Memory into History - de Oliveira, Jacyan Castilho (Revista Brasileira de Estudos da Presença, 2022)
Between the Dance that Registers and the Library that Dances, Dimenti turns Memory into History – Created in 1998, the Dimenti Group from Salvador (BA) produces artistic works that blur the lines between scenic languages and modes of production, until finally becoming Dimenti Produções Culturais, a creative environment that today encompasses audiovisual, editorial and phonographic productions, events and festivals, among others. In this article the focus is on Tombé (2001) and Biblioteca de dança (2017) dance performances, as examples of this diversified production. The aim is to point out, from the perspective of its members, the authorial traits that persist in Dimenti’’s creative trajectory, such as comicality, non-linearity and the incorporation of an ideological discourse of otherness.